Dynamic strain aging in the intermediate temperature regime of near-α titanium alloy, IMI 834: Experimental and modeling. (1st January 2022) - Agrawal, Priyanka; Karthikeyan, S.; Makineni, Surendra Kumar; Gault, Baptiste; Banerjee, Dipankar
Abstract: A dynamic strain aging (DSA) regime is established for a near- α titanium alloy with a microstructure consisting of 80% equiaxed α, 15% lamellar α and 5% β with silicon in solid solution through a series of constant strain rate tests carried out in tension from 5 × 10 −2 to 5 × 10 −6 s −1 in the temperature range of 623–823 K. Transmission electron microscopy shows jogged screw dislocations within slip bands dominating the dislocation structure in this domain. Strain accumulation occurs by conservative jog glide along the length of screw dislocations due to line tension forces. We estimate the solute concentration accumulating at these edge jogs on arrest during their thermally activated glide over static solute obstacles. The domain of DSA is then predicted using Friedel's model to obtain the stress required to break the jogs free from the solute atmosphere. There is a good agreement between model and experimental data showing a DSA peak in the temperature range of 673–723 K. The solute species responsible for DSA from the model are C and Si, but dominated by C in this temperature and strain rate regime. Atom probe tomography demonstrates C and Si segregation at the dislocations, strongly supporting the model. Graphical abstract: Image, graphical abstract